Management of peritonitis in children receiving chronic peritoneal dialysis - Schaefer, Franz (Pediatric drugs, 2003)
Bacterial peritonitis is a major threat to long-term peritoneal membrane function in pediatric patients receiving chronic peritoneal dialysis (CPD). This review summarizes the demographics, risk factors, and current recommendations regarding diagnostic procedures, management, and prevention of peritonitis in children.